The relationship between metabolic dysfunction-associated fatty liver disease and the incidence rate of extrahepatic cancer - Wei, Suosu; Hao, Yanrong; Dong, Xiaofeng; Huang, Junzhang; Huang, Kai; Xie, Yujie; Liu, Hongjun; Wei, Chunyu; Xu, Jinan; Huang, Wei; Dong, Lingguang; Yang, Jianrong (Frontiers in Endocrinology, 2023)
Background: The association between metabolic dysfunction-associated fatty liver disease (MAFLD) and cancer development, especially extrahepatic cancers is yet unknown. The aim of this study was to investigated the cancer incidence rates in MAFLD and analyzed the association between MAFLD and development of cancers. Methods: This historical cohort study included subjects who underwent ultrasonographic detection of hepatic steatosis at a tertiary hospital in China from January 2013 to October 2021. MAFLD was diagnosed according to the international expert consensus statement. Cox proportional hazards regression model was used to assess the association between MAFLD and development of cancers. Results: Of 47,801 subjects, 16,093 (33.7%) had MAFLD. During the total follow-up of 175,137 person-years (median 3.3 years), the cancer incidence rate of the MAFLD group was higher than that of the non-MAFLD group (473.5 vs. 255.1 per 100,000 person-years; incidence rate ratio [IRR] 1.86; 95% confidence interval [CI] 1.57–2.19; p <0.001). When adjusted for age, sex, smoking status and alcohol status, MAFLD showed a moderate association with labium, uterus, cervical & ovary cancer in females (HR 2.24; 95% CI 1.09–4.60; p = 0.029), bladder cancer (HR 4.19; 95% CI 1.15–15.27; p = 0.030) and thyroid cancer (HR 3.64; 95% CI 1.82–7.30; p = 0.000). Conclusion: MAFLD was associated with the development of labium, uterus, cervical & ovary cancer, bladder cancer and thyroid cancer.